ORDER OF DIFFICULTIES ON SIMPLE PAST TENSE MASTERY BY EIGHTH GRADERS OF SMPN 29 SAMARINDA - Mahmudding Mahmudding (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
This study is aimed at seeing the order of difficulties on simple past tense based on the level of difficulties of the test items made by the second year students of SMPN 29 Samarinda. This study used descriptive design, the researcher took 100 students as a sample of this study. The research instrument was 40 items test in simple past tense mastery. The study discovered two findings. First, the mastery based on the mean score is 61,75. The score is indicated as a fair level or C score. It means that from 100 students, 35 or 35% failed and 65 or 65% were successful on simple past tense. Second, the order of difficulties on simple past tense was negative sentences is the first order (59.4%),  irregular (42.7%), the verb be (37.1%) and  regular (14.8%).